Pakeliran Wayang Babad Lakon Harya Penangsang: dari Kethoprak ke Pakeliran - Lilik Agung; Dewanto Sukistono; Retno Dwi Intarti (Institut Seni Indonesia Yogyakarta, 2021)
AbstractThe work of wayang babad performance Harya Penangsang is aimed at presenting the story of Harya Penangsang which originally came from the kethoprak performance into the wayang babad performance. In addition to the transformation from kethoprak to wayang babad performance, this work aims to present the work of Harya Penangsang figures. The concept transformation of Sapardi Djoko Damono is used as a frame of mind. The development of this work began by observing and analyzing the performance of the wayang performance about Harya Penangsang that had been staged by several dalang. In addition, it also tracks the character of Harya Penangsang through kethoprak stories and in some serat babad. Next is a draft storyline, which includes events and settings. From this, the character plans the characterization, theme, and trust and visualization of the characters.AbstrakKarya pakeliran wayang babad lakon Harya Penangsang ini bertujuan menghadirkan kisah Harya Penangsang yang semula berasal dari pertunjukan kethoprak ke dalam pertunjukan wayang babad. Selain transformasi dari kethoprak ke pakeliran wayang babad, karya ini bertujuan menyajikan garap tokoh Harya Penangsang. Konsep alih wahana Sapardi Djoko Damono digunakan sebagai kerangka pikir. Penggarapan karya ini dimulai dengan mengamati dan menganalisis pergelaran lakon wayang babad lakon Harya Penangsang yang pernah dipentaskan oleh beberapa dalang. Selain itu juga melacak karakter Harya Penangsang melalui kisah-kisah kethoprak dan dalam beberapa serat babad. Selanjutnya dibuat draft alur cerita, yang mencakup peristiwa dan setting. Dari sini, pengkarya merencanakan penokohan, tema, dan amanah serta visualisasi tokoh-tokohnya.